Reducing the Procurement Lead Time for Agreed Stock Item in Procurement Division of PT Alami Mandala Indonesia - Ganes Agni Wibisono; Akbar Adhi Utama (Eduvest - Journal of Universal Studies, 2026)
This study investigates the persistent delays in procurement lead time for Agreed Stock Items (AGSI) within the Procurement Division of PT Alami Mandala Indonesia (AMI). AGSI refers to repeat-order materials that are already agreed upon in specification and usage, and therefore, ideally should be processed swiftly. However, data revealed that the actual PR to PO lead time consistently exceeds the company's OKR target of 14 days, creating operational inefficiencies, potential equipment downtime, and financial losses. This issue is especially critical in the context of AMI's mining operations, which are highly dependent on timely and uninterrupted supply of materials to sustain production activities. A mixed-methods research approach was adopted, combining qualitative insights from semi-structured interviews with procurement personnel and quantitative analysis of historical procurement data from SAP ERP systems spanning 2023–2024. Through this approach, the study identified key bottlenecks including repetitive manual bidding processes for the same items, incomplete or unclear material specifications, limited supplier pools, and logistical difficulties stemming from the company's remote mining sites. These issues were further structured and analyzed using a Fishbone Diagram and Current Reality Tree (CRT) to identify root causes and systemic weaknesses. To address these challenges, a set of alternative solutions was developed and evaluated using a weighted scoring method based on four criteria: potential for lead time reduction, implementation effort, cost implications, and impact on material availability. Among these, the implementation of Long Term Agreements (LTAs) with key suppliers was identified as the most feasible and impactful solution.